1991
DOI: 10.1128/jb.173.17.5449-5456.1991
|View full text |Cite
|
Sign up to set email alerts
|

The osa gene of pSa encodes a 21.1-kilodalton protein that suppresses Agrobacterium tumefaciens oncogenicity

Abstract: The incompatibility group W plasmid pSa suppresses Agrobacterium tumefaciens oncogenicity (J. Loper and C. Kado, J. Bacteriol. 139:591-596, 1979). The oncogenic suppressive activity was localized to a 3.1-kb region of pSa by TnS mutagenesis and deletion analysis. Within this fragment, a 1.1-kb subclone bearing oncogenic suppressive activity was subjected to further characterization. Nucleotide sequencing of the 1.1-kb fragment revealed a 570-bp open reading frame (ORF1) that has a coding capacity for a protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…The RSF1010 derivatives pJB31 and pJW323 were shown previously to suppress tumorigenesis by the octopine-type strain A348 on N. tabacum (tobacco) and K. daigremontiana (4,33), whereas pSa inhibited transformation of numerous plant species by both strain C58 (7,9,11,23) and strain A208 (19), which contain a nopalinetype Ti plasmid, and by strains A348 (19) and 1D1 (11), which contain an octopine-type Ti plasmid. Oncogenic suppression by pSa was more effective on A. tumefaciens C58 than suppression of strain 1D1 was (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RSF1010 derivatives pJB31 and pJW323 were shown previously to suppress tumorigenesis by the octopine-type strain A348 on N. tabacum (tobacco) and K. daigremontiana (4,33), whereas pSa inhibited transformation of numerous plant species by both strain C58 (7,9,11,23) and strain A208 (19), which contain a nopalinetype Ti plasmid, and by strains A348 (19) and 1D1 (11), which contain an octopine-type Ti plasmid. Oncogenic suppression by pSa was more effective on A. tumefaciens C58 than suppression of strain 1D1 was (11).…”
Section: Discussionmentioning
confidence: 99%
“…The osa (oncogenic suppressive activity) gene of pSa is sufficient to inhibit plant transformation (7,9). This phenomenon, called oncogenic suppression, resembles fertility inhibition of conjugative plasmid transfer by plasmids of different incompatibility groups (16,24,27).…”
mentioning
confidence: 99%
“…osa is part of an operon. Previous sequence analyses of the 3.1-kb DNA fragment revealed the presence of four orfs, one of which was osa (6,7). No obvious promoters or potential binding sites for a positive regulator (e.g., inverted repeats) were found in the regions where promoters are usually found with respect to the translational start site of each ort.…”
Section: Resultsmentioning
confidence: 99%
“…orf-3 is followed by the 570-bp osa gene. Although previous studies have indicated that osa plays a major part in oncogenic inhibition (6), the contribution of each upstream gene, such as nuc, to this activity has remained unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation